Developing markets for water reallocation: Revisiting the experience of Spanish water mercantilización. (June 2015) - Hernández-Mora, Nuria; Del Moral, Leandro
Highlights: Reviews the experience of water mercantilización in Spain. Focuses on the case study of water permit sales using Tajo–Segura transfer infrastructure in 2005–2008 drought. Describes the process of institutional development necessary to facilitate the operation of water markets. Shows that the outcome of mercantilización favors the interests of powerful groups. Abstract: Economic instruments are being promoted as a desirable alternative to public sector action in the allocation and management of natural resources. A wide body of literature has developed that critically analyzes this phenomenon as part of a wider project of 'neoliberalization of nature', trying to uncover the underlying rationale and commonalities of geographically specific phenomena. The case of water is at the vanguard of these processes and is proving to be particularly contentious. In the European Union water policies are increasingly emphasizing the application of economic instruments to improve the allocative equity and economic efficiency in the use of scarce resources. However, there are few analyses of how these instruments are really working on the ground and whether they are meeting their objectives. This paper aims to contribute to this debate by critically analyzing the experience with water markets in Spain, the only country in the European Union where they are operative. It looks at water permit sales during the 2005–2008 drought period using the Tajo–Segura transfer infrastructure. The paper describes how the institutional process of mercantilización of water works in practice in Spain. It shows that the use of markets requires an intense process of institutional development to facilitate and encourage their operation. These institutions tend to favor the interests of clearly identifiable elites, instead of the public interest they supposedly promote.